'Walking the tightrope' : pregnant women & malnutrition in Aotearoa : how the Sustainable Development Goals 2 & 5 reframe the current discourse - Raven, Briony (Massey University, 2018)
In 2015 a new global development platform, called the Sustainable Development Goals (SDGs) were launched and for the first-time developed nations were included in the development agenda. Poverty, food insecurity and inequality in the developed world are now encompassed within this global platform and are open to international standardisation and critique. This presents significant challenges for developed/western countries who have previously looked outwards at developing nations as the subject of the development gaze. This desk-based study explores how developed countries are responding to this new paradigm by looking at a case study in Aotearoa, New Zealand. This case study focusses on SDGs 2: empowerment & 5: food security to address how we can reframe the current discourse on pregnant women and malnutrition in Aotearoa. Using a critical discourse analysis (CDA) to interrogate the current discourse across three platforms this study has three key findings (themes). Firstly, pregnant women are singularly responsible for ensuring adequate nutrition; secondly, a healthy pregnancy requires women to be educated to adhere to complex food guidelines; and lastly the use of fear and monitoring of women to motivate adherence. An overarching or ‘grand theme’ which is summarised as ‘walking a tightrope’ finds that women are expected to achieve unrealistic nutritional targets within the realities of everyday life. However, the SDG’s provide an opportunity to reframe the ‘problem’ of malnutrition in pregnancy to one of food security and empowerment of women. This ‘reframing’ more appropriately addresses the complexity of issues which underlies malnutrition and provides a framework for government and social policy to robustly address malnutrition for pregnant women. This report therefore concludes that this new global focus on developed countries presents a significant opportunity for them to adopt development frameworks to achieve the SDGs.